The classification as a differentiating variable of the characteristics of the set action in volleyball formative stages - González-Silva, J.; Moreno Domínguez, A.; Fernández-Echeverría, C.; Claver Rabaz, F.; Moreno Arroyo, P. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The aim of the study was to determine the association between the teams’ classification and the setting variables, in both genders. The study sample was comprise of a total of 1638 setting actions, carried out by the 34 teams (16 male, 18 female) participating in the Under-16 Spanish Championship. The study variables were the classification and the setting variables (setting zone, type of set, setting technique, set´s area, tempo of set). The results showed significant association between the classification and the setting zone, setting technique and setting efficacy, in both genders; the classification and the type of set, in male gender; and the classification and the tempo of set, in female gender. These results highlighted that, even though the set is an intermediate action, it have a fundamental importance in the game, and it may affect to the final classification of the team in competition.